MODEL PEMBELAJARAN TEMATIK INTEGRATIF BERBASIS KURIKULUM 2013 DI MADRASAH IBTIDAIYAH - Jefryadi, Jefryadi (PD PGMI se Indonesia, 2020)
The 2013 curriculum-based integrative thematic learning model is a learning strategy that involves several subjects into a learning theme that uses an interdisciplinary approach to provide meaningful experiences to students in the learning process. The application of this learning model requires adequate infrastructure and mature teacher understanding concepts. Integration and success in this learning model can be seen from the aspect of understanding of the learning model, aspects of the learning strategy, and aspects of the use of media in learning. Because every teacher has their own characteristics in conveying learning to students, in order to achieve learning objectives. Therefore the writer wants to examine more deeply how the application of the 2013 curriculum-based integrative thematic learning model in MIN Yogyakarta II and MI Ma'had Islamy Kotagede Yogyakarta?. This study aims to determine the mastery of integrative thematic learning models, the strategies applied and the media used by teachers in the application of integrative thematic learning models. This research is categorized in the type of field research (Field Research) which is descriptive with qualitative research methods using theories about integrative thematic learning models then proceed to drawing conclusions. The results showed that in general these two institutions had applied the integrative thematic learning model well. The teacher's mastery of the learning model and the methods used by the teacher in linking learning material are already good so that learning becomes a unified and meaningful whole for students. Then the strategies used by the teacher in planning learning activities, preliminary activities, core activities and closing activities are quite diverse and adjusted to the needs and interests of students. The media used have their respective characteristics and are always adapted to the learning material to be taught. Although they have differences in learning strategies and the media used in teaching, however, they have the same goal of achieving success in teaching so that the expected goals can be achieved and provide meaningful experiences to students.